Letter (copy) : Spanish medical aid - Tewson, Vincent
032-0015-001 Secretary's. HVT/FC/MN/2427. 21st June, 1940. Mr. H. Campbell, c/o Mr. Chesney, 184 Battlefield Road, Longside, Glasgow. Dear Mr. Campbell, SPANISH MEDICAL AID. We have your note of the 19th instant and am glad that you have cabled Mr. Cornwell in accordance with the conversation which we had last week. We have not yet heard anything from Mr. Cornwell but immediately we do so we will get into touch with you. I am not sure whether you will be be turning to London before your departure but if you do I shall be very glad to see you again. Yours sincerely, Assistant Secretary. 292/946/32/15